2003
DOI: 10.1029/2002jb002127
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical analysis of sliding of rough surfaces

Abstract: [1] I used a model proposed by Greenwood and Williamson [1966], who analyzed closure between a rough surface and a smooth surface under normal stress, to analyze the growth of slip under increasing shear stress, normal stress remaining constant. The two bodies are elastic half-spaces, one rough and one smooth, and Coulomb friction resists slip at sliding contacts. The elastic and dissipative components of the constitutive relation in shear depend upon statistical parameters which describe the topography of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…Mindlin and Deresiewicz [9] show for a single asperity that cyclic loading is almost elastic at small amplitudes, and further that the compliance of the contact to cyclic loading does not depend on the shear stress acting on the joint. Walsh [7] found that these observations held as well for rough surfaces.…”
Section: Dynamic Stressing---elastic Componentmentioning
confidence: 59%
See 2 more Smart Citations
“…Mindlin and Deresiewicz [9] show for a single asperity that cyclic loading is almost elastic at small amplitudes, and further that the compliance of the contact to cyclic loading does not depend on the shear stress acting on the joint. Walsh [7] found that these observations held as well for rough surfaces.…”
Section: Dynamic Stressing---elastic Componentmentioning
confidence: 59%
“…To make the calculations easier, we have chosen to approximate the distribution g(h/λ) of asperity heights h by a negative exponential e -h/λ (see (4)), where λ is found by fitting the exponential to the appropriate part of the distribution function. We make the further simplification that all asperities have the same tip radius R. The justification for using these approximations and the procedure for estimating λ are discussed by Walsh [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The model we use was proposed by Greenwood and Williamson [1966] to analyze the closure between rough surfaces under normal stress. Walsh [2003] used Greenwood and Williamson's model in a study of sliding between rough surfaces under constant normal stress. In the analysis here, we analyze deformation of rough surfaces, again using Greenwood and Williamson's model, when both applied normal stress and shear stress are increased simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Walsh [2003] derived the theoretical constitutive relationship for slip under applied shear stress, the normal stress remaining constant, using Greenwood and Williamson's [1966] model as the basis of his study. He found that the final form of the constitutive relationship was relatively insensitive to choice taken for the probability density function g(h/l) for asperity heights or for the radii of asperity tips; that is, uncertainties in experimental sliding data masked the differences between various theoretical constitutive relationships.…”
Section: Introductionmentioning
confidence: 99%